The psychosocial impact of acne vulgaris - Hazarika, Neirita; Archana, M (Indian journal of dermatology, 2016)
Background: Acne vulgaris causes erythematous papulopustular lesions in active stage and often leave behind residual scarring and pigmentation. Its onset in adolescence may add to the emotional and psychological challenges experienced during this period. Aims: To assess the impact of acne on the various psychosocial domains of daily life. Materials and Methods: This was a prospective, cross-sectional study done in the dermatology out-patient department of a tertiary care hospital from January to March 2015. A total of 100 consecutive, newly diagnosed patients of acne vulgaris, aged 15 years and above were included in this study. The relationship between acne vulgaris and its sequelae was analyzed with ten different domains of daily life by using dermatology life quality index (DLQI) questionnaire. Results: Females (56%), 15-20 year olds (61%), facial lesions (60%), and Grade II acne (70%) were most common. Acne scars were noted in 75% patients, whereas 79% cases had post-acne hyperpigmentation. Thirty-seven percent patients had DLQI scores of (6-10) interpreted as moderate effect on patient's life. Statistically significant correlation (P < 0.05) found were as follows: Physical symptoms with grade of acne; embarrassment with site and grade of acne; daily activities with grade of acne and post-acne pigmentation; choice of clothes with site of acne; social activities with gender, site and grade of acne; effect on work/study with grade of acne; interpersonal problems with site and post-acne pigmentation; sexual difficulties with grade of acne. Limitation: It was a hospital-based study with small sample size. Conclusion: Significant impact of acne and its sequelae was noted on emotions, daily activities, social activities, study/work, and interpersonal relationships. Assurance and counseling along with early treatment of acne vulgaris is important to reduce disease-related psychosocial sequelae and increase the efficacy of treatment.